Reduction of olfactory sensitivity during normobaric hypoxia. Issue 4 (August 2018) - Huppertz, Tilman; Freiherr, Jessica; Olzowy, Bernhard; Kisser, Ulrich; Stephan, Jutta; Fesl, Gunther; Haegler, Kathrin; Feddersen, Berend; Fischer, Rainald; Mees, Klaus; Becker, Sven
Abstract: Objective: Acute mountain sickness (AMS) is caused by a low partial pressure of oxygen and may occur above 2500 m. The aim of this research was to evaluate olfactory and gustatory abilities of healthy subjects during baseline conditions and after seven hours of normobaric hypoxia. Methods: Sixteen healthy subjects were assessed using the Sniffin' Sticks, as well as intensity and pleasantness ratings. Gustatory function was evaluated utilizing the Taste Strips. Experiments were carried out under baseline conditions (518 m altitude) followed by a second testing session after seven hours of normobaric hypoxia exposure (comparable to 4000 m altitude). Results: During normobaric hypoxia olfactory sensitivity and intensity estimates were significantly reduced. Conclusions: We conclude that normobaric hypoxia leads to a significant decrease of olfactory sensitivity and intensity ratings.